Chitosan as a biocontrol agent against the pinewood nematode (Bursaphelenchus xylophilus). Issue 5 (7th August 2014) - Nunes da Silva, M.; Cardoso, A. R.; Ferreira, D.; Brito, M.; Pintado, M. E.; Vasconcelos, M. W.; Woodward, S.
Summary The pine wilt disease (PWD) is caused by Bursaphelenchus xylophilus and poses great environmental and economic challenges. Thus, the development of sustainable techniques for the control of this epidemic disease is of major importance. This work aimed at evaluating if the application of different molecular weight (MW) chitosans as a soil amendment could be used to control the PWD in maritime pine (Pinus pinaster, very susceptible to the disease) and stone pine (Pinus pinea, less susceptible). At the end of the experimental period (24 days after inoculation), P. pinaster and P. pinea untreated plants presented ca. 3825 ± 100 and 70 ± 47 nematodes, respectively. In P. pinaster, the high‐MW chitosan prompted the most drastic results, inducing a 21.9‐fold reduction in nematodes numbers, whereas in P. pinea, the most effective was the low MW chitosan, which reduced nematodes numbers up to 7‐fold, compared with untreated plants. P. pinea seems to be highly resistant to the disease, presenting nematode numbers up to 54.6‐fold lower than P. pinaster and less severe chlorophyll loss (ca. 2‐fold).